Cytochrome P450 1 family: the roles of 1A1, 1A2 and 1B1 in drug metabolism - Guengerich, F. Peter (Henry Stewart Talks, 2007)
Family 1 P450, Substrates, Regulation, Polymorphisms, Levels of activity and cancer, Adverse drug reactions, P450 systems and drug development, Molecular epidemiology in cancer issues
Updated at 2016/07/31